EFEKTIVITAS PRIMARY DRESSING HIDROFOBIK SEBAGAI PADA LUKA DIABETIC FOOT ULCER DIRUMAH ETN CENTERE MAKASSAR - Awalia Putri; Wa Ode Sri Asnaniar; Fatma Jama (Jurnal Kesehatan, 2025)
Diabetic Foot Ulcer (DFU) is one of the most serious chronic complications in people with diabetes mellitus. DFU is an open wound in the foot tissue that arises due to a combination of neuropathy, peripheral vascular disorders (ischemia), and susceptibility to infection. Hydrophobicity can increase effectiveness by up to 4% in attracting fungi and hydrophobic bacteria, thereby preventing the formation of biofilms in wounds. Modern dressings Cutimed Sorbact is a type of antimicrobial dressing that has strong hydrophobic properties. This study aims to determine the effectiveness of hydrophobic primary dressings on diabetic foot ulcers at the ETN Center Makassar. This study used a case report study method with a descriptive approach. This study only used one sample, namely one patient (case report) with Diabetic Foot Ulcer who was treated at the ETN Center Makassar. DFU wound care with hydrophobic dressings showed good results. The wound area decreased from 0.35 cm² (20/08/2025) to 0.25 cm² (23/08/2025). Exudate decreased from 30% to 20%, biofilm from 25% to 20%, granulation tissue increased from 60% to 65%, while necrotic tissue, slough, and epithelium remained at 5% each. This indicates a positive wound healing process. Treatment of Diabetic Foot Ulcers (DFU) using hydrophobic dressings effectively accelerates the healing process, characterized by reduced wound area, reduced exudate and biofilm, and increased granulation tissue/healthy tissue. This suggests that hydrophobic dressings may be a good choice in DFU wound management.